The Relationship of Lifestyle with Hypertension in Bumiayu Kabupaten Bojonegoro - Linda Miftahul Jannah; Ernawaty Ernawaty (Jurnal Berkala Epidemiologi, 2018)
Background: Hypertension becomes a serious problem since one in three adults worldwide suffers from hypertension. Hypertension is the third highest cause of death in Indonesia at all ages with the proportion of deaths of 6.83%. Purpose: This study aims to determine the relationship of lifestyle with hypertension in Dusun Sendang Anyar and Tambakrame Desa Bumiayu Kecamatan Baureno Kabupaten Bojonegoro. Methods: This research was done for a month from July to August 2017. This research type is descriptive with cross sectional research design. The population study were 150 family heads who have at least one family member aged ≥40 years. Sampling method using cluster random sampling, obtained sample of 101 family heads. Independent variable in this study is hypertension, while the dependent variable is lifestyle that includes sports habits, smoking, consumption of salted fish, spinach, banana, and frying food. Data analysis using chi square statistic test with significance level of 95% and α = 5%. Results: This study showed that the variables related to hypertension were sports habit (p = 0.01), smoking (p = 0.01), consumption of salted fish (p = 0.01), consumption of spinach (p = 0.01), consumption of banana (p= 0.02). Variable unrelated to hypertension was consumption of frying food (p = 0.23). Conclusion: There were correlation between exercise habits, smoking, consumption of salted fish, consumption of spinach, and consumption of banana with hypertension.